American Journal of Aging Science and Research 2020
DOI: 10.46439/aging.1.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical function and perceived stress among U.S. Chinese older adults

Abstract: Objectives Physical function impairment can cause great stress to older adults. The purpose of the study is to investigate the association between self-reported and directly-observed physical function on perceived stress among U.S. Chinese older adults. Methods Data were from the Population Study of Chinese Elderly in Chicago (PINE) of 3,157 Chinese older adults who were 60 and above in the Greater Chicago Area. Self-reported and directly-observed physical function meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The reason may be that the static balance training lasted only 12 weeks, and the time was too short to improve the perceived stress of older adults in the community. Studies have shown that the main sources of perceived stress for older adults in the community are major diseases, obesity, sleep disorders, and ideological conflicts [ 10 , 44 ]. Sensory-based static balance training cannot fundamentally solve the above problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason may be that the static balance training lasted only 12 weeks, and the time was too short to improve the perceived stress of older adults in the community. Studies have shown that the main sources of perceived stress for older adults in the community are major diseases, obesity, sleep disorders, and ideological conflicts [ 10 , 44 ]. Sensory-based static balance training cannot fundamentally solve the above problems.…”
Section: Discussionmentioning
confidence: 99%
“…Up to the age of 60, balance ability can remain relatively intact; however, it gradually diminishes at an approximate rate of 16% every decade thereafter [ 5 ]. The decline in balance significantly increases the risk of falls among older adults and impairs their capacity to effectively perform ADLs [ 6 – 8 ], thus increasing their negative aging attitudes and perceived stress [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with physical limitations may be more vulnerable to stress and have fewer resources to cope with stress, resulting in higher stress levels (de Rekeneire and Volpato 2015). Higher scores of objective physical functioning (including chair stand, tandem stand, timed walking, and overall measurement) were associated with lower levels of perceived stress in older adults (Chao et al 2020). Rueggeberg et al (2012) examined perceived stress's role in the association between physical activities and older adults' physical health.…”
Section: Well-being and Physical Activitymentioning
confidence: 96%
“…Therefore, effective interventions to reduce older adults' physical and cognitive functional decline are public health priorities (Freedman et al 2017;Zlatar et al 2019). Research has shown that apart from physical bene ts, psychological indices like well-being (Steptoe et al 2015), life satisfaction (Gacek et al 2023), happiness (An et al 2020), resilience (Martinez-Moreno et al 2020), perceived stress (Chao et al 2020) can also be positively affected by exercise intervention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, negative perceived stress (NPS) can induce an individual to adopt an emotion-focused coping strategy that involves maladaptive coping mechanisms. Therefore, NPS can affect an individual’s IADL dependence [ 27 , 28 ]. By contrast, positive perceived stress (PPS) involve a positive appraisal of stressful situations and can prompt an individual to adopt a problem-solving strategy that influences their self-care behaviors.…”
Section: Introductionmentioning
confidence: 99%